Troublesome behaviour in the classroom : meeting individual needs - McManus, Mick, 1943- (Routledge, 2002)
The fully updated second edition of Troublesome Behaviour in the Classroom is the most comprehensive and practical guide available on the subject of behaviour management in schools. Distinguished by Mick McManus' lively and witty writing style, it is packed with practical ideas, activities, insights and solutions which will be invaluable to all teacher training students and classroom teachers.